Assumptions about the dynamics sources and mechanisms of plate tectonic activities - Chen, Ziyun; Li, Tianbin; Gao, Meiben; Chen, Wei (Frontiers in Earth Science, 2025)
The problem of the driving source and power mechanism of plate motion remains a major scientific issue in urgent need of resolution. Based on the isostatic hypothesis model proposed by G.B. Airy in 1855, this study puts forward the crustal isostatic model based on the self-weight stress field and the assumption of the dynamic source of plate movement. It is believed that the plate movement in the crustal layer is the result of deep magma activities, and the mode of activity is mainly laminar flow. In terms of the dynamic mechanism, the assumption of the magma flow mechanism is proposed. It is believed that the magma flow is driven by the magma density gradient, and the magma density varies with depth. By using the model and assumptions in this paper, the two mechanical mechanisms of surface rupture and block movement are analyzed. Taking the Chengdu block in Western Sichuan as an example, the correlation between magma flow, regional stress field, large-scale displacement and tectonic activities is analyzed. The analysis results are in good agreement with the actual situation, effectively explaining the morphology and activities of typical fault activity structures in this region. The research results are helpful for people to further understand the tectonic activities of the Earth.